Simulação da dinâmica dos movimentos executados por um Manifold - Cunha, Vicente Cordeiro da (2019)
The installation of large-sized subsea equipments, such as manifolds, has already been done successfully by PETROBRAS, since last decade. However, in the pendulous installation method (PIM), for instance, instabilities of manifold motion occur during its descent to sea bottom. Thus, this work has at its main objective the study of the dynamic motions performed by a manifold. To do that, it was proposed a mathematical model to describe the body motions, a set of experimental tests to obtain the added mass and drag coefficients and a program to solve numerically the Equations of Motion.